Peran Program Dirosah Masaiyah dalam Peningkatan Kompetensi Dakwah Mahasiswa Prodi KPI STIBA Ar Raayah Sukabumi - Hidayat, Tatang; Priyadi, Gian Resa; Istianah, Istianah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study was to analyze the role of the dirosah masaiyah program on the da'wah competence of students of the STIBA Ar Raayah 4th semester Islamic Communication and Broadcasting Study Program in 2022-2023. This research uses a qualitative approach and descriptive method. Data were collected using participant observation techniques. The results showed that the extracurricular da'wah activities of dirosah masaiyah were dirosah tarbawiyah, riyadhoh, yaumul haasuub, dirosah tajwid, and dirosah ushul fiqh. The da'wah activities of dirosah masaiyah play a role in improving the da'wah competence of students of the Islamic Communication and Broadcasting Study Program of STIBA Ar Raayah semester 4 in 2022-2023 in terms of intellectual, physical, personal, social, and spiritual. The supporting factors are enthusiasm/motivation, curiosity, sense of responsibility, a sense of filial piety towards parents, love, class fanaticism, a sense of competition, attendance, respect for the speaker and also closeness to the speaker. While the inhibiting factors are the lack of student interest, the lack of suitability of some presenters or activities, the absence of presenters, the absence of good organization, student boredom, the absence of presence and also the existence of the presence itself which makes students feel forced and not sincere in participating in activities. The implication is that it is necessary to make a policy of student participation and their achievements in the dirosah masaiyah program will add academic value.